The right of non-Muslims to form political parties and alliances and the opposition = حق غير المسلمين في تشكيل الأحزاب والتحالفات السياسية والمعارضة - Abu Dalal, Ahmad Basim Saadi; Mat Jubri@Shamsuddin, Mustafa (Al Hikmah Research and Publication Centre, 2023)
This article addresses an important issue related to the political rights of non-Muslims in Islamic jurisprudence. The issue of the rights of non-Muslims is one of the topics that Islam's enemies use to attack it, accusing the state of limiting the rights of non-Muslims. Furthermore, the contradiction of contemporary scholars' fatwas on political rights of non-Muslims in several issues is a reason to investigate these topics to show the model of the noble Islamic rule that respects diversity. Studies that have dealt with the rights of non-Muslims in Islamic society have generally addressed them, including books such as "Non-Muslims in Islamic Society" by Dr. Yusuf al-Qaradawi, "Citizenship Rights" by Sheikh Rashid Al-Ghannouchi, and "Political Rights and Freedoms in Islamic Law" by Dr. Rahil Grayebah, among other valuable books in their fields. However, they did not address this topic specifically. Therefore, this study adopts a descriptive, inductive, and analytical research methodology. The study concludes with several recommendations, the most important of which is that non-Muslims living in Islamic countries and holding their nationality have the right to citizenship, which gives them the right to enjoy political rights. It is also permissible for non-Muslims to form political parties and alliances, and they have the right to opposition, provided it does not contradict the principles of Islamic law.